Analysis of Peanut (Arachis Hypogeae L) Farming in Buae Village, Watang Pulu District, Sidenreng Rappang Regency - Rauf, Andi Sulkifli; Irmayani, Irmayani; Nurhaedah, Nurhaedah (UNIVERSITAS NEGERI MAKASSAR, 2021)
This study aims to determine (1) how much is the cost of peanut farming, (2) how much income is obtained from peanut farming, (3) how much is the feasibility level of peanut farming. This type of research used in this research is descriptive quantitative. The data collection methods used were observation, questionnaires, and interviews. The data analysis used was the B / C Ratio. Primary data which is the result of interviews with respondent farmers is tabulated to determine the cost and income of peanut farmers in Buae Village, the amount of costs used by peanut farmers is divided into three, among others: (1) the cost of labor outside the family (reel issued) of Rp. 5,465,316 and family workers (calculated) of Rp. 2,900,000, (2) the cost of production facilities is Rp. 2,321,457.31 (3) fixed costs of Rp. 345,299.67 total costs incurred by farmers of Rp. 8,132,073.21 / Ha. The amount of revenue is Rp. 18,071,018.06 / Ha. The amount of income received is Rp. 9,938,944.85 / Ha based on the calculation of B / C ratio shows 1.22 indicating that peanut farming in Buae Village is feasible to be developed where each expenditure is Rp. 1 can give you a profit of Rp. 1.22.